Distinct subfamilies of primate L1Gg retroposons, with some elements carrying tandem repeats in the 5' region. - Lloyd, J A (1988)
Two subfamilies of L1 elements, differing dramatically in the first 1.2 kb of sequence at their 5' ends, were identified in the prosimian primate, Galago garnetti. Interesting patterns of sequence similarity were observed between the galago subfamilies, and with the L1s from human and from another prosimian, the slow loris. Furthermore, members of one of the subfamilies have six to eight tandemly repeated units of 73 bp, starting about 730 bp from their 5' ends. Such tandem repeats have not been reported in other primate L1s, but a striking sequence similarity was found between the galago tandem repeats and those previously described at the 5' termini of some mouse L1s [Loeb, D. D. et al. Mol. Cell. Biol. 6, 168-182, 1986]. Although the similar sequence indicates a shared, conserved function, the galago repeats are sub-terminal and therefore cannot serve as portable RNA polymerase II promoters, as has been suggested for the mouse tandem repeats.